Chemical composition changes of two water apple (Syzygium samaragense) - Shamsuddin, Rosnah; Wong, W. K.; Muda, Noraziah; Hassan, Osman (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Changes in physical properties (weight, size, colour and weight loss) and chemical properties (proximate analysis, TSS, pH, freezing point, total acidity and sugar content) of two water apple (Syzgium samaragense) cultivars, Semarang Rose and Kristal Taiwan were evaluated during ripening at 10°C and 50% RH. The results showed that the Kristal Taiwan cultivar was larger in size and weight but smaller in length compared to Semarang Rose. The Semarang Rose cultivar was sweeter than Kristal Taiwan. In this study, data obtained suggests that the water apple fruit can be stored at cold storage until 19 days.